Research on the Scheme of Churn Suppression for Wireless Mesh Network - Guangxue Yue; Dan Luo; Jiansheng Liu; Mingming Li (Dianxin kexue)
Through analysis of behavioral characteristics of churn nodes in wireless mesh network, a schema was proposed to improve the speed limit caused by congestion. The basic idea of the approach is to heuristically select the service nodes with lowest churn rate when it accesses the streaming media, where the churn rate is predicted through a utility function. In addition, a failure recovery scheme for the churn nodes with heavy congestion was proposed. A node was considered failure and replaced with another peer by migrating the services on it whenever the node encounters congestion and its churn rate exceeded a predefined threshold. Simulation results show that the scheme can not only efficiently solve the problem of high congestion,single failure,and low delivery efficiency,but also significantly improve the QoS of the wireless mesh network,at the same time to verify the objective existence of churn.